'Dissidence' in Holocaust Memorials in Literature: Jáchym Topol's The Devil's Workshop (Chladnou zemí). (3rd July 2015) - Chew, Geoffrey
Abstract: Established Czech precedent has made the town of Terezín an important literary symbol of Holocaust memory, used in the 1960s to construct myths of Czech innocent victimhood. Jáchym Topol's novel, The Devil ' s Workshop (2009), returns to the theme with great originality, avoiding such myths by using a compromised first-person Czech narrator, who is involved in setting up 'dissident' commemorative museums at Terezín and in Belarus. These draw on documented accounts of real atrocities for their authenticity. Competitive in national terms, commercialized, and ethically compromised, they are finally, arguably inevitably, silenced. Topol's 'truth-telling' is discussed in the context of Theodor W. Adorno's criticism of committed Holocaust literature, Benedict Anderson's interpretation of museums as commercialized constructions of nationality, and Timothy Snyder's historical account of the killings in Eastern Europe; the ambiguous pessimism of his novel stands up well to criticism and, it is argued, has lessons even for historians of the Holocaust.